Cellular effects of acute direct current stimulation: somatic and synaptic terminal effects. (16th April 2013) - Rahman, Asif; Reato, Davide; Arlotti, Mattia; Gasca, Fernando; Datta, Abhishek; Parra, Lucas C.; Bikson, Marom
Key points The diversity of cellular targets of direct current stimulation (DCS), including somas, dendrites and axon terminals, determine the modulation of synaptic efficacy. Axon terminals of cortical pyramidal neurons are two–three times more susceptible to polarization than somas. DCS in humans results in current flow dominantly parallel to the cortical surface, which in animal models of cortical stimulation results in synaptic pathway‐specific modulation of neuronal excitability. These results suggest that somatic polarization together with axon terminal polarization may be important for synaptic pathway‐specific modulation of DCS, which underlies modulation of neuronal excitability during transcranial DCS. Abstract Transcranial direct current stimulation (tDCS) is a non‐invasive brain stimulation technique to modulate cortical excitability. Although increased/decreased excitability under the anode/cathode electrode is nominally associated with membrane depolarization/hyperpolarization, which cellular compartments (somas, dendrites, axons and their terminals) mediate changes in cortical excitability remains unaddressed. Here we consider the acute effects of DCS on excitatory synaptic efficacy. Using multi‐scale computational models and rat cortical brain slices, we show the following. (1) Typical tDCS montages produce predominantly tangential (relative to the cortical surface) direction currents (4–12 times radial direction currents), even directly under electrodes. (2) Radial current flow (parallel to the somatodendritic axis) modulates synaptic efficacy consistent with somatic polarization, with depolarization facilitating synaptic efficacy. (3) Tangential current flow (perpendicular to the somatodendritic axis) modulates synaptic efficacy acutely (during stimulation) in an afferent pathway‐specific manner that is consistent with terminal polarization, with hyperpolarization facilitating synaptic efficacy. (4) Maximal polarization during uniform DCS is expected at distal (the branch length is more than three times the membrane length constant) synaptic terminals, independent of and two–three times more susceptible than pyramidal neuron somas. We conclude that during acute DCS the cellular targets responsible for modulation of synaptic efficacy are concurrently somata and axon terminals, with the direction of cortical current flow determining the relative influence.